Evaluation of herbicide mixtures for weed control in soybean (Glycine max) in southern Nigeria - Avav, T; Okereke, O U; Abutu, I U (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during 1991 and 1992 to evaluate herbicide mixtures for controlling weeds in soybean [Glycine max(L.) Merr.] at Makurdi in Nigeria. Post-emergence application of sethoxydim + imazethapyr (0.37 + 0.10 kg/ha) as tank-mix gave the highest grain yield (2.47 tonnes/ha). followed by fluazifop + imazcethapyr(O.25 + O. 10 kg/ha) (2,46 tonnes/ha): pre-emergence application of imazaquin + pendimethalin (0.72 + 1.25 kg/ha) (2.44tonnes/ha). imazethapyr+ pendimethalin(0.23 + 1.13 kg/ha) (2.20 tonnes/ha) and metobromuron + metolachlor (1.25 + 1.25 kg/ha) (2.12 tonnes/ha). Increased grain yield was on account of reduced weed biomass. Those yields were comparable to those from plots weeded with hoe 2 and 3 times. Weed-control efficiency was 60.7-77.2% for herbicides and 61.4- 82.9% for weeding with hoe. Uncontrolled growth of weeds in the unweeded control reduced the grain and stover yields by 51 and 66% respectively.